Functions of autophagy in the tumor microenvironment and cancer metastasis. (1st February 2018) - Mowers, Erin E.; Sharifi, Marina N.; Macleod, Kay F.
Abstract : Macro‐autophagy is an ancient and highly conserved self‐degradative process that plays a homeostatic role in normal cells by eliminating organelles, pathogens, and protein aggregates. Autophagy, as it is routinely referred to, also allows cells to maintain metabolic sufficiency and survive under conditions of nutrient stress by recycling the by‐products of autophagic degradation, such as fatty acids, amino acids, and nucleotides. Tumor cells are more reliant than normal cells on autophagy for survival in part due to their rapid growth rate, altered metabolism, and nutrient‐deprived growth environment. How this dependence of tumor cells on autophagy affects their progression to malignancy and metastatic disease is an area of increasing research focus. Here, we review recent work identifying critical functions for autophagy in tumor cell migration and invasion, tumor stem cell maintenance and therapy resistance, and cross‐talk between tumor cells and their microenvironment. Abstract : Autophagy is upregulated as tumors progress to become malignant and this review addresses how autophagy modulates cancer metastasis. Specifically, we examine the critical role played by autophagy in tumor cell migration and invasion, in maintaining the cancer stem cell phenotype and tumor cell dormancy as well as how autophagy affects interactions of tumor cells with components of the tumor microenvironment. Finally, we discuss how these functions make autophagy inhibition an attractive therapeutic option for metastatic cancers.